2021
DOI: 10.3390/medicina57090977
|View full text |Cite
|
Sign up to set email alerts
|

The Approach of Pregnant Women to Vaccination Based on a COVID-19 Systematic Review

Abstract: Background and Objectives: Pregnant women are more likely to develop a more severe course of COVID-19 than their non-pregnant peers. There are many arguments for the safety and efficacy of COVID-19 vaccines in pregnant women. The aim of this study is to conduct a systematic review concerning the approach of pregnant women towards vaccination against COVID-19, with particular regard to determinants of vaccination acceptance. Materials and Methods: Articles were reviewed in which the aim was to evaluate—via a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 53 publications
7
93
0
12
Order By: Relevance
“…Furthermore, lower economic status and physical health and already being a mother were related to higher psychological distress among the Arab women. The findings regarding economic status and physical health are consistent with the results of previous studies (Gur et al, 2020 ; Januszek et al, 2021 ; Matsushima & Horiguchi, 2020 ) and may indicate that less favorable background characteristics, which put pregnant women at greater risk for psychological distress even in routine times (Goletzke et al, 2017 ; Koleva et al, 2011 ), are even more telling after prolonged coping with a pandemic that has serious implications for their health, social, and economic status. In the case of mothers, the need to care for their children while contending with the pandemic and their pregnancy concurrently may place enormous demands on them and exhaust their ability to cope well with the situation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, lower economic status and physical health and already being a mother were related to higher psychological distress among the Arab women. The findings regarding economic status and physical health are consistent with the results of previous studies (Gur et al, 2020 ; Januszek et al, 2021 ; Matsushima & Horiguchi, 2020 ) and may indicate that less favorable background characteristics, which put pregnant women at greater risk for psychological distress even in routine times (Goletzke et al, 2017 ; Koleva et al, 2011 ), are even more telling after prolonged coping with a pandemic that has serious implications for their health, social, and economic status. In the case of mothers, the need to care for their children while contending with the pandemic and their pregnancy concurrently may place enormous demands on them and exhaust their ability to cope well with the situation.…”
Section: Discussionsupporting
confidence: 92%
“…However, it might indicate a degree of mistrust in the vaccine in this population, so that those who had already recovered from COVID‐19 felt more immune to the virus. Another possibility is that anxiety about COVID‐19 was a motivating factor to obtain vaccination against COVID‐19, as has been suggested in a systematic review concerning the association between COVID‐19 anxiety of the extent of compliance to be vaccinated against it among pregnant women (Januszek et al, 2021 ). As this is the first study to explore this issue, future studies are warranted to deepen our understanding of the psychological mechanisms underlying pregnant women's fears of infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in England, a large reduction in vaccination rates of up to 43.7% was recorded [ 31 ]. The variability of acceptance of the vaccine against COVID-19 in pregnant women is also wide, between 29.7% and 77.4%, geographically dependent, and related to acceptance of the influenza vaccine [ 32 ]. These results suggest that promoting MV against COVID-19 together with influenza may be beneficial for increasing vaccination coverage of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Skjefte M et al, the level of vaccine acceptability amongst pregnant women was around 52% [14]. In a systematic review led by Januszek S et al, over 33 studies that appealed the acceptability of SARS-CoV-2 vaccination for pregnant or lactating individuals was between 29.7 and 77.4% [15]. In our country, a study conducted by Citu IM et al concerning vaccine acceptability for pregnant women observed a hesitancy of 52.5% vs. 40.3% for non-pregnant individuals [16].…”
Section: Discussionmentioning
confidence: 99%